A Modular Ligation Strategy for Asymmetric Bivalent Nucleosomes Trimethylated at K36 and K27. (12th March 2019) - Guidotti, Nora; Lechner, Carolin C.; Bachmann, Andreas L.; Fierz, Beat
Abstract: In nature, individual histones in the same nucleosome can carry identical (symmetric) or different (asymmetric) post‐translational modification (PTM) patterns, increasing the combinatorial complexity. Embryonic stem cells exhibit "bivalent" nucleosomes, some of which are marked by an asymmetric arrangement of H3K36me3 (an activating PTM) and H3K27me3 (a repressive PTM). Here we describe a modular synthetic method to access such asymmetrically modified nucleosomes and show that H3K36me3 inhibits the activity of the methyltransferase PRC2 locally while still prolonging its chromatin binding time. Abstract : Access all areas : Asymmetric nucleosomes are a key feature of stem cell chromatin. Here a modular and traceless chemical strategy to control the supramolecular assembly of bivalent nucleosomes asymmetrically modified at K27 and K36, is described. It is shown that the trimethylation of K36 hinders PRC2 activity while extending its binding time to chromatin fibers.